TELAAH FILM â€œDANCE WITH WOLVESâ€ MELALUI TEORI GENRE DALAM PERSPEKTIF ISLAM - Setiawan, Arief Tri; Bakti, Andi Faisal; Muhtadi, Muhtadi; Hermansah, Tantan; Rizky, Kiky (KOMUNIKE, 2021)
Not many western genre films are made in the film industry, because of not many ideas can be explored. The Dance With Wolves film is a western genre film and is not made as a religious film. This film also does not intend to include Islamic principles. The most interesting is that this western genre film was made with high imagination and creativity. By using the theory of genre from Branston and Stanford, it was then studied further through the concept and living rules â€‹â€‹in the Al-Qur'an and Hadith. The results of this study illustrated a struggle (jihad) in the elements of the story (repertoires of elements) that united and inspired feelings. Also in the verisimilitude genre theory, a statement of belief (ilmul yaqin) raised in the truth of Allah's creation. Furthermore, through the cultural context theory, it could be seen that at-tamaddun exists.